A variational characterization of a hyperelastic rod with hard self-contact - Hoffman, Kathleen A.; Seidman, Thomas I. (Nonlinear analysis, 2011)
We consider an elastic rod, modeled as a curve in space with an impenetrable surrounding tube of radius ρ , subject to a general class of boundary conditions. The impossibility of self-intersection is then imposed as a family of scalar constraints on the physical separation of nonlocal pairs of points on the rod. Thus, the usual variational formulation of energy minimization is considered in a context of nonconvex, nonsmooth optimization. We show the existence of minimizers within suitably defined homotopy classes associated with both the centerline and the frame along the rod. The principle results are then concerned with derivation of first-order necessary conditions for optimality and some consequences of these for the contact forces and for regularity.